Managing transboundary waters in extreme environments: the role of international actors in Africa - Giordano, Mark; Lautze, Jonathan F. (2009)
Africa is a continent of extreme water resource environments with arguably the greatest spatial and temporal natural water supply variability in the world. Africa is also a land of transboundary waters. With the exception of island states, every African country has territory in at least one transboundary river basin. These basins cover 62% of Africa's total land area, and virtually every one greater than 50,000 km2 crosses at least one national boundary. The management of these transboundary waters in conditions of such variability has been made even more complex by the unique political and economic history of the continent, in particular as related to the involvement of outside actors. In the first half of the 20th century this involvement was related to colonialism. From the second half to the present, it has involved bi-lateral and international donors, lenders and international NGOs. In this paper, we examine the impacts of this influence by first reviewing the development of transboundary water law in Africa. We then examine how the global norms now mentioned in African law, in particular equity in water allocation, have actually influenced agreement content. Finally, we examine the extent to which influences wielded by international actors are a logical response to conditions in Africa's international basins. The results highlight the tangible influences of international actors on the orientation and content of basin level agreements and suggest the use of greater discretion in the application of international paradigms to water management agreements in extreme environments.